Optimization of fermentation conditions to enhance the physicochemical, microbiological and sensory attributes of tomato juice using probiotic strains Lactobacillus acidophilus and Bifidobacterium lactis - Wan Abdullah, Wan Nur Najibah; Padmanabhan, Kousalya; Chong, Kah Hui; Abdul Jabar, Nor Azmiraah; Jiang, Shan; Pan, Wanyu; Nor-Khaizura, Mahmud Ab Rashid (SAGE Publications, 2025)
Background: The demand for ready-to-drink products offers nutritional characteristics and health benefits has increased tremendously due to the evolving consumer preferences in selecting foods or beverages with health benefits. Aim: This study aimed to produce fermented tomato juice at different sucrose concentrations and fermentation times and to evaluate the microbiological, physicochemical and sensory properties at two different parameters. Methods: The lactic acid bacteria (LAB), Lactobacillus acidophilus and Bifidobacterium lactis, were incorporated into the tomato juice at 1% (w/w). The fermentation was conducted at 42°C at different times of 0, 2, 4 and 6 h. Results: The results showed that samples with 1.5% sucrose displayed the most stable viability of LAB (5.15 log CFU/mL) as the fermentation time increased. As the fermentation time increased, it was discovered that the pH value gradually decreased (pH 4.321–4.333), the titratable acidity fluctuated insignificantly (p > 0.05) and the total soluble solids content decreased too. The physicochemical evaluation showed that samples with 2.0% sucrose, fermented for 6 h, had better physicochemical properties than others. Lastly, according to the conducted sensory evaluation on the acceptance tests with the involvement of 50 panellists, it was found that the sample with 2.0% sucrose concentration and fermented for 4 h was the most preferred. Conclusion: Considering all the conducted evaluations, it could be deduced that the fermented tomato juice with 2.0% sucrose and fermented for 6 h was selected as the most favourable compared to other samples.